Randomised controlled trial to investigate the effectiveness of local oestrogen treatment in postmenopausal women undergoing pelvic organ prolapse surgery (LOTUS): a pilot study to assess feasibility of a large multicentre trial. Issue 9 (10th September 2020) - Verghese, Tina Sara; Middleton, Lee; Cheed, Versha; Leighton, Lisa; Daniels, Jane; Latthe, Pallavi Manish
Abstract : Objective: To evaluate the feasibility of a multicentre randomised controlled trial (RCT) comparing oestrogen treatment with no oestrogen supplementation in women undergoing pelvic organ prolapse (POP) surgery. Design and setting: A randomised, parallel, open, external pilot trial involving six UK urogynaecology centres (July 2015–August 2016). Participants: Postmenopausal women with POP opting for surgery, unless involving mesh or for recurrent POP in same compartment. Intervention: Women were randomised (1:1) to preoperative and postoperative oestrogen or no treatment. Oestrogen treatment (oestradiol hemihydrate 10 μg vaginal pessaries) commenced 6 weeks prior to surgery (once daily for 2 weeks, twice weekly for 4 weeks) and twice weekly for 26 weeks from 6 weeks postsurgery. Outcome measures: The main outcomes were assessment of eligibility and recruitment rates along with compliance and data completion. To obtain estimates for important aspects of the protocol to allow development of a definitive trial. Results: 325 women seeking POP surgery were screened over 13 months and 157 (48%) were eligible. Of these, 100 (64%) were randomised, 50 to oestrogen and 50 to no oestrogen treatment, with 89 (44/45 respectively) ultimately having surgery. Of these, 89% (79/89) returned complete questionnaires at 6 months and 78% (32/41) reported good compliance with oestrogen. No serious adverse events were attributable to oestrogen use. Conclusions: A large multicentre RCT of oestrogen versus no treatment is feasible, as it is possible to randomise and follow up participants with high fidelity. Four predefined feasibility criteria were met. Compliance with treatment regimens is not a barrier. A larger trial is required to definitively address the role of perioperative oestrogen supplementation. Trial registration number: ISRCTN46661996 .